2009
DOI: 10.1017/s1744552309990036
|View full text |Cite
|
Sign up to set email alerts
|

Transnational Hindu law adoptions: recognition and treatment in Britain

Abstract: This article examines how the adoption of children under Hindu law in India is regarded by British private international law and immigration law. Through an analysis of case-law, it focuses particularly on how British judges regard the legitimacy of exclusion by the British immigration control system of children who have been adopted under a 'foreign' legal system which essentially permits private adoption arrangements. Examining the background to the regime of Indian Hindu law adoptions (which applies to Sikh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…However, interference in existing family life must first be established under Art 8(1) and that will depend upon the facts, while, under Art 8(2), the child's interests must compete with other considerations including immigration control. 122 Occasionally, in intra-family adoptions, it may be found that serious and compelling family or other considerations make exclusion undesirable. 123…”
Section: (B) Childrenmentioning
confidence: 99%
“…However, interference in existing family life must first be established under Art 8(1) and that will depend upon the facts, while, under Art 8(2), the child's interests must compete with other considerations including immigration control. 122 Occasionally, in intra-family adoptions, it may be found that serious and compelling family or other considerations make exclusion undesirable. 123…”
Section: (B) Childrenmentioning
confidence: 99%
“…One of the key themes in this research field literature is migrants' legal transnationalism, that is, how migrants' pre-migratory cultural and normative repertoires (values, attitudes towards the law, entrenched behavioural patterns, accustomed social practices and informal norms) influence their everyday lives and experiences in their host society (Ballard, 2006;Kubal, 2013a;Menski, 1993;Shah, 2009). However, the existing studies on migrants' legal transnationalism largely focus on the case studies of immigrant communities in "established countries of immigration" such as the United States, Australia, Canada and Western European countries.…”
Section: Introductionmentioning
confidence: 99%
“…The development of Hindu law began with Sruti, which was written in the tenth century B.C. It then inspired the Dharma Sastra book, which is a collection of pure laws rather than Sruti/Smrti [9], including the fourth periodization starting from Krtha Yuga with Manawadharma sastra, Treta Yuga with Gautama Dharmasastra, Dwipara Yuga with Samkha Likhita Dharmasastra, and Kali Yuga with Parasara Dharmasastra [10]. The concretization of Hindu law begins with the Manu eras and has influenced subsequent periods, including the Majapahit era, with the introduction of legal reforms toward a modified Manawadharmasastra based on Majapahit conditions.…”
Section: Reintroduce Hindu Law: Concept Critique and Its Importance To The Indonesian Lawmentioning
confidence: 99%